Abducens Nerve Palsy Due to Coronavirus Disease (COVID-19) - Goenawan, Kristian; Mahayana, Indra Tri (Jurnal Kedokteran Meditek, 2023)
The main causes of N.VI paralysis in adults are microvascular disease, vasculopathy, tumors, and inflammatory conditions. However, recent studies suggest that neurotropic viruses may be the etiology of N.VI paralysis. COVID-19 also has neurotropic and neuroinvasive capabilities that make the eye susceptible to bilateral optic neuritis, papilledema, and cranial nerve paralysis, the most common of which is abducens nerve palsy. The aim of this literature review is to review studies that describe the occurrence of abducens nerve palsy in COVID-19 patients. The literature search began in the period April-May 2022 from the Google Scholar database (https://scholar.google.com/). This mini review used the AMSTAR (Assessment of Multiple Systemic Review 2, including randomized and nonrandomized studies) checklist and reviewers independently agreed on the selection of eligible studies and reached consensus regarding which studies to include with inclusion criteria. This mini review found that 75% of cases were strongly associated with viral infection and 25% of cases were strongly associated with COVID-19 vaccination. Only 50% of cases report improvement in abducens nerve palsy. This has the implication that with the increasing prevalence of COVID-19 worldwide, ophthalmologists should be aware that abducens nerve palsy may be part of COVID-19.